Zimbabwe Public Expenditure Review 2017 : Volume 3. State Enterprises and Parastatals - Government of Zimbabwe; World Bank (World Bank, Washington, DC, 2017)
Zimbabwe is at a critical juncture. After dollarization and favorable economic factors fueled arecovery during 2009-12, Zimbabwe today faces slowing growth, a financial crisis, increasingly erratic weather patterns and rising poverty and inequality. To help respond to these issues, the Government of Zimbabwe (GoZ) has sought to examine and ultimately better manage its public expenditures, with a view to ensuring public spending is effective, efficient, equitable, and well-targeted to the needs of its changing population, especially the poor.